Conversion of Elbow Arthrodesis to Total Elbow Arthroplasty: A Case Report and Literature Review. (June 2022) - Cutler, Holt S; Heineman, Nathan; Hurd, Aaron; Koehler, Daniel; Bass, Robert; Schacherer, Timothy
Elbow arthrodesis is a salvage operation designed to relieve pain and enable weight bearing in young patients with painful arthritic joints who have failed all other treatment modalities. Unfortunately, elbow arthrodesis is poorly tolerated by many patients because there is no fusion position that accommodates all activities of daily living. As indications for elbow arthroplasty expand and implant design improves, patients living with elbow arthrodesis may seek conversion to arthroplasty to regain a functional range of motion. Only one case of elbow arthrodesis to elbow arthroplasty conversion has been reported in the English literature to date. We present the case of a 58 year old male, five years status post elbow arthrodesis, unable to perform his ADLs adequately, who was successfully converted to a total elbow arthroplasty. Indications, contraindications, and technical pearls are discussed.